TRAINING OF SPECIALISTS IN THE DIRECTION OF ^PSYCHOLOGY PERFORMANCE MANAGEMENT»: SPECIFIC, PROBLEMS, CHALLENGES - Irina Belasheva; Marine Yesayan (Вестник Северо-Кавказского федерального университета)
This article discusses the features of the training of specialists in the direction of37.05.02 - Psychology of performance in the current political, social and economic conditions, taking into account the competence-based approach to the implementation of educational programs. A theoretical analysis of the constructs of «competence» and «competency» and their refraction in the educational-methodical maintenance of disciplines and practices. It presents the specifics ofpreparation of experts on the psychology ofperformance management in the North Caucasus Federal University and associated with it challenges and problem areas.